Unguisin G, a new kynurenine-containing cyclic heptapeptide from the sponge-associated fungus Aspergillus candidus NF2412. Issue 40 (1st October 2020) - Li, Wei; Jiao, Fang-Wen; Wang, Jia-Qi; Shi, Jing; Wang, Ting-Ting; Khan, Salman; Jiao, Rui-Hua; Tan, Ren-Xiang; Ge, Hui-Ming
Graphical abstract: Highlights: One new kynurenine-containing cyclic heptapeptide named unguisin G was isolated from the sponge-derived fungus . The structure was elucidated by the spectroscopic data of HRESIMS and NMR. The absolute configuration of unguisin G was confirmed by Marfey's reaction. Abstract: One new cyclic heptapeptide containing non-proteinogenic amino acid residues kynurenine and γ -aminobutyric acid, named unguisin G, as well as three known congeners unguisins A, E and F, were isolated from a sponge-derived fungus Aspergillus candidus NF2412. The structures were elucidated by comprehensive spectroscopic analyses of HRESIMS and NMR data. The absolute configuration of amino acid residues of 1 was determined by advanced Marfey's method. All compounds were evaluated on antimicrobial activities against nine pathogens by the agar diffusion method.